A Location-Based Outcome Analysis of the Most Common Microsurgically Clipped Cerebral Aneurysms: A Single-Center Experience. Issue 1 (5th February 2021) - Nisson, Peyton L; Meybodi, Ali Tayebi; Berger, Garrett K; Thompson, Austen; Morshed, Ramin A; Lawton, Michael T
ABSTRACT: BACKGROUND: Intracranial aneurysms of the anterior communicating artery (AComA), posterior communicating artery (PComA), and the middle cerebral artery (MCA) comprise the majority of all aneurysms encountered and treated by vascular neurosurgeons. OBJECTIVE: To analyze and compare outcomes between these locations using multivariable logistic regression and to assess what clinical features may differ between them. METHODS: Solitary aneurysms microsurgically clipped by the senior author were included from a prospective database of patients treated between January 2010 and April 2013 at a tertiary academic medical center. Neurological status was assessed using the modified Rankin Scale (mRS). Neurological outcomes were dichotomized, with mRS scores 0-2 considered "good" and 3-6 considered "poor." RESULTS: A total of 196 patients were treated; 69 aneurysms were located at the MCA, 77 at the AComA, and 50 at the PComA. A total of 48% (97/196) of patients presented with a ruptured aneurysm and 14% (25/180) were considered large. PComA was more commonly presented as a ruptured aneurysm (64%) compared to AComA (56%) and MCA (28%) ( P ≤ .001),  and when ruptured, PComA aneurysms were 1.6 times more likely to experience a favorable outcome compared to MCA aneurysms ( P  = .01). Regression analysis revealed PComA was associated with a lower risk for poor outcomes (odds ratio [OR] 0.19, P  = .01) controlling for age, presentation type, and vasospasm. CONCLUSION: Patients who underwent microsurgical clipping of ruptured PComA aneurysms experienced significantly better outcomes, while those with MCA aneurysms suffered the worst. Further investigation on this topic and the potential reasons that may account for these differences is warranted.